2019 34th Annual ACM/IEEE Symposium on Logic in Computer Science (LICS) 2019
DOI: 10.1109/lics.2019.8785659
|View full text |Cite
|
Sign up to set email alerts
|

The Logic of Action Lattices is Undecidable

Abstract: Action logic is the algebraic logic (inequational theory) of residuated Kleene lattices. This logic involves Kleene star, axiomatized by an induction scheme. For a stronger system which uses an ω-rule instead (infinitary action logic) Buszkowski and Palka (2007) have proved Π 0 1 -completeness (thus, undecidability). Decidability of action logic itself was an open question, raised by D. Kozen in 1994. In this article, we show that it is undecidable, more precisely, Σ 0 1 -complete. We also prove the same compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The former is a commutative counterpart of results by Buszkowski and Palka [1,18]. The latter is a commutative counterpart of an earlier result by the author [9,11].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The former is a commutative counterpart of results by Buszkowski and Palka [1,18]. The latter is a commutative counterpart of an earlier result by the author [9,11].…”
Section: Discussionsupporting
confidence: 70%
“…A similar idea was used to prove undeciability in the non-commutative case, for ACT [9]. In the commutative situation it is even more straightforward, since Minsky computation here is represented directly, without a detour through totality of context-free grammars [1,9].…”
Section: σ 0 1 -Completeness Of Commact 41 Circular Proofs For Circul...mentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, it has been shown that associativity often leads to undecidability. Buszkowski [5] and Palka [20] have shown that the logic of all * -continuous action lattices (the ones where, roughly, Kleene star is equivalent to an infinite disjunction) is undecidable; Kuznetsov [15] established recently that the logic of all action lattices is undecidable as well. His proof applies also to Pratt's Action Logic.…”
Section: Introductionmentioning
confidence: 99%